Dataset on evolution analysis of splenic transcriptome in bighead carp and silver carp - Guoxi Li; Yinli Zhao; Shuang Guo; Bianzhi Liu; Yi Chen; Xiangli Sun; Jianxin Feng (Data in Brief, 2019)
Bighead carp (Aristichthys nobilis) and silver carp (Hypophthalmichthys molitrix) are closely related species in the subfamily Xenocypridinae within Cyprinidae, and they are also two of the four most important pond-cultured fish species in China. The ability to resist some diseases often differs significantly in silver carp and bighead carp during fishery production. However, the evolutionary divergence of the immune defense functions in these two species is still not understood at the molecular level. The data presented in this article are related to the research article entitled “Comparative analysis of spleen transcriptome detects differences in evolutionary adaptation of immune defense functions in bighead carp and silver carp” (Li et al., 2018). Please refer to this data article for interpretation of the data. Data provided in this submission comprise the Ka/Ks ratios of orthologs as well as adaptive evolution genes, expression levels of orthologs, and TPM value of genes expressed only in spleen of bighead carp or silver carp. These data provide a better understanding of the differences in evolutionary adaptation of immune defense functions in bighead carp and silver carp.